“(Jardim Canadá) é tudo nosso, mas um é um e dois é dois” : a ressignificação coletiva da categoria de bairro e a produção de localidades no Jardim Canadá (Nova Lima - MG) - Stephanie Mesquita Assaf (2016)
Jardim Canadá is a planned neighborhood situated in Nova Lima, Minas Gerais concluded in the late 50's. Despite being accepted by the State as a single neighborhood two distinct regions can be pointed: Jardim Canadá 1 and Jardim Canadá 2. These unofficial regions are not recognized by the State and and cannot be found in official records. Here we discuss how places can be planned in one manner while its daily life lived in a very different one. We present how in a recent time interval new localities are being produced in this neighborhood in a contextof a rapid process of social change within this profile (especially in the newer part Jardim Canadá 2). Roughly, his process known as gentrification, concerns the replacement of the poorest by more affluent groups.